Customary Leadership and Power Relations in the Preservation of the Wonosadi Customary Forest: A Foucauldian Analysis of the Onggoloco Myth - Wahyudi, Mhd Andika; Sumbayak, Michael Gorvb; Utama, Dandy Yoga; Masela, Liana Thrice; Irwan, Imel; Putri, Felisitas Daratra Parama (Journal of Cultural Analysis and Social Change, 2026)
This study aims to analyze how the Onggoloco myth is employed by customary leaders as a leadership strategy in preserving the Wonosadi Customary Forest, while also explaining the configuration of power relations among customary leaders, local communities, and nature through the perspective of Michel Foucault’s theory of power relations. The research adopts a qualitative method with a descriptive interpretative approach, drawing on secondary data obtained through an extensive literature review, including academic publications, cultural documents, and findings from previous studies. The analysis reveals that customary leadership in Wonosadi is not coercive in nature but operates through symbolic discourse and local knowledge systems that cultivate ecological awareness and voluntary compliance within the community. The Onggoloco myth functions as a form of productive environmental power that generates social discipline, ethical norms, and subtle forms of resistance to external interventions. Consequently, customary leadership represents a productive mode of power that sustains harmony among humans, nature, and spirituality.